PENTINGNYA DIGITALISASI LAYANAN PUBLIK DESA - Herman Sahputra; Rolly Yesputra; Adi Prijuna Lubis; Fairuz Furqon (Smart Education, 2024)
Abstract: Villages in Indonesia face significant challenges in providing efficient and transparent public services, such as bureaucratic inefficiency, lack of transparency, limited accessibility, and low community participation. This community service program proposes the digitalization of public services in Teluk Dalam Village using the Participatory Action Research (PAR) method to address these issues. The proposed solutions include the digitalization of village administration, development of a village information platform, implementation of e-government services, and training and education for village officials and the community. These steps are expected to improve the efficiency of public services, transparency, accessibility, and community participation in village governance. Through the implementation of this program, Teluk Dalam Village is expected to become an exemplary village in successfully implementing the digitalization of public services, providing significant benefits to the community, and enhancing the quality of village governance. Keyword: Digitalization; Public Services; Transparency; Accessibility; Community Service Abstrak: Desa-desa di Indonesia menghadapi tantangan signifikan dalam penyelenggaraan layanan publik yang efisien dan transparan, seperti birokrasi yang berbelit-belit, kurangnya transparansi, keterbatasan aksesibilitas, dan rendahnya partisipasi masyarakat. Program pengabdian masyarakat ini mengusulkan digitalisasi layanan publik di Desa Teluk Dalam melalui metode Participatory Action Research (PAR) untuk mengatasi permasalahan tersebut. Solusi yang ditawarkan mencakup digitalisasi administrasi desa, pengembangan platform informasi desa, penerapan layanan e-government, serta pelatihan dan edukasi bagi perangkat desa dan masyarakat. Langkah-langkah ini diharapkan dapat meningkatkan efisiensi layanan publik, transparansi, aksesibilitas, dan partisipasi masyarakat dalam proses pemerintahan desa. Dengan pelaksanaan program ini, Desa Teluk Dalam diharapkan dapat menjadi contoh desa yang berhasil mengimplementasikan digitalisasi layanan publik, memberikan manfaat signifikan bagi masyarakat, dan meningkatkan kualitas pemerintahan desa.. Kata kunci: Digitalisasi; Layanan Publik; Transparansi; Aksesibilitas; Pengabdian Masyarakat